Strategi 3M Plus Mencegah Dan Mengatasi Demam Berdarah Dengue (DBD) DiDusun 3 Desa Sukasari, Kecamatan Air Periukan, Kabupaten Seluma - Anggraini, Reri; Kurniati, Susi; Nurhdayati, Indah; Tranado, Hengki; Suyanto, Jipri (Utami Publisher, 2025)
Dengue Hemorrhagic Fever (DHF) is an endemic disease in Indonesia, including in Seluma Regency, especially Hamlet 3 Sukasari Village. The public's low awareness of the importance of preventing and controlling mosquito nests is one factor in the spread of this disease. A community-based outreach program using the 3M Plus approach was carried out to increase community knowledge and attitudes in preventing dengue fever. The methods used include direct counseling, leaflet distribution, and Clean Friday mutual cooperation. The 3M Plus strategy (Drain, Cover, Bury) is implemented actively by involving community leaders and health cadres. The results of the activity show an increase in understanding and participation of residents in maintaining environmental cleanliness to prevent dengue fever.